2016
DOI: 10.1007/s11684-016-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma symptoms in Golestan schoolchildren aged 6–7 and 13–14 years in Northeast Iran

Abstract: Asthma is the most common chronic disease among children, and its incidences are often imminent among elementary schoolchildren. This study aimed to examine the prevalence of asthma symptoms in Golestan schoolchildren aged 6-7 and 13-14 years in Northeast Iran. The prevalence rate was compared according to age group (aged 6-7 years vs. aged 13-14 years) and gender (male vs. female). In this cross-sectional study, 1706 Iranian schoolchildren aged 6-7 and 13-14 years in Golestan Province were enrolled. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
4
10
2
Order By: Relevance
“…However, the prevalence of doctor‐diagnosed asthma reported in this study is within the range of those reported in the global pediatric asthma prevalence surveys on African children with reported proportions from 2.5% in Ethiopia and Burkina Faso to almost 10% in Swaziland . The prevalence of doctor‐diagnosed asthma from recent cross‐sectional studies from other low‐ and middle‐income countries were as high as 7.5% in Iran, 6% in India, 4.8% in China, 3% in Senegal, 2.5% in Mongolia, to 2% in Georgia …”
Section: Discussionsupporting
confidence: 71%
“…However, the prevalence of doctor‐diagnosed asthma reported in this study is within the range of those reported in the global pediatric asthma prevalence surveys on African children with reported proportions from 2.5% in Ethiopia and Burkina Faso to almost 10% in Swaziland . The prevalence of doctor‐diagnosed asthma from recent cross‐sectional studies from other low‐ and middle‐income countries were as high as 7.5% in Iran, 6% in India, 4.8% in China, 3% in Senegal, 2.5% in Mongolia, to 2% in Georgia …”
Section: Discussionsupporting
confidence: 71%
“…25 A recent study in children and adolescents reported that the prevalence of asthma in adolescents (aged 13-14 years) was significantly higher than that in schoolchildren aged 6-7 years. 26 This study also found that the severity of asthma in girls was higher than that in boys aged 13-14 years. In older adults, two phenotypes are usually observed: patients with longstanding asthma who develop additional airflow limitation, and those who develop late-onset asthma.…”
Section: Sex Differences In Lung Diseasessupporting
confidence: 56%
“…This instrument was developed by the researcher based on previous studies (3,(22)(23)(24)(25). This data consists of the schoolchildren's general information, their demographical status, gender, age, race, and family history of asthma.…”
Section: Study Instruments Demographical Datamentioning
confidence: 99%